2017
DOI: 10.1021/acs.jmedchem.7b01295
|View full text |Cite|
|
Sign up to set email alerts
|

Design of MC1R Selective γ-MSH Analogues with Canonical Amino Acids Leads to Potency and Pigmentation

Abstract: Melanoma is a lethal form of skin cancer. Skin pigmentation, which is regulated by the melanocortin 1 receptor (MC1R), is an effective protection against melanoma. However, the endogenous MC1R agonists lack selectivity for the MC1R and thus can have side effects. The use of noncanonical amino acids in previous MC1R ligand development raises safety concerns. Here we report the development of the first potent and selective hMC1R agonist with only canonical amino acids. Using γ-MSH as a template, we developed a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 50 publications
(82 reference statements)
2
26
0
Order By: Relevance
“…28 Recently, it was demonstrated that analogs of γ-MSH, which had 16-fold selectivity for MC1R compared with other melanocortin receptors, induced rapid (1 minute) and reversible (1 day) pigmentation after intraperitoneal injection using the Anolis carolinensis lizard model of cutaneous pigmentation. 29 The development of more selective α-MSH analogs with the potential for topical administration is ongoing. 23 An α-MSH analog with increased specificity for the MC1R that can be delivered topically would be more convenient for patients than a drug administered by injection and has the potential for a decreased side-effect profile.…”
Section: Melanocortin 1 Receptor Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Recently, it was demonstrated that analogs of γ-MSH, which had 16-fold selectivity for MC1R compared with other melanocortin receptors, induced rapid (1 minute) and reversible (1 day) pigmentation after intraperitoneal injection using the Anolis carolinensis lizard model of cutaneous pigmentation. 29 The development of more selective α-MSH analogs with the potential for topical administration is ongoing. 23 An α-MSH analog with increased specificity for the MC1R that can be delivered topically would be more convenient for patients than a drug administered by injection and has the potential for a decreased side-effect profile.…”
Section: Melanocortin 1 Receptor Agonistsmentioning
confidence: 99%
“…Analogs of γ-MSH, with 16-fold selectivity for MC1R versus other melanocortin receptors, were recently shown to induce rapid (1 minute) and reversible (1 day) pigmentation after intraperitoneal injection using the Anolis carolinensis lizard model of cutaneous pigmentation 29 . Development of more selective α-MSH analogs with the potential for topical administration is ongoing 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, using NMR and computational aid drug design combined with chimeric receptor studies we can design more bioavailable and druggble selective hMC1R ligands rationally. As an example, we successfully developed only natural amino acid made peptide, [Leu3, Leu7, Phe8]-γ-MSH-NH 2 , which is a potent selective hMC1R agonist with 24nM binding affinity and 4.5 nM functional activity [9] (Figure 1 .) and many other hMC1R selective agonists such as Ac-His-DPhe(4-CF 3 )-Nle-Trp-NH 2 which are more druggable and bioavailable with 339nM binding affinity and 10nM functional activity. [10] NMR structure demonstrated that Ac-His-DPhe(4-CF 3 )-Nle-Trp-NH 2 is β -turn structure.…”
Section: Resultsmentioning
confidence: 99%
“…38 For comparison, the latter compound has a pIC 50 of 7.6 and a pEC 50 of 8.3 at hMC1R and modest (16-fold) selectivity over hMC4R. 38 Whereas several of our analogs had varying degrees of activity at MC3R and MC4R, only one had appreciable binding to MC5R ( 15 ). The initial selectivity profiles observed in a largely nonoptimized molecular framework suggests plenty of scope for further pharmacological optimization.…”
Section: Discussionmentioning
confidence: 99%